Constructing an Empirically Derived Measure for Customer Contact - Kellogg, Deborah L.; Chase, Richard B. (Management Science, 1995)
This research provides an empirically derived measurement model for customer contact, a widely used construct in service management. The model was created by applying two psychometric scaling techniques, Multidimensional Scaling (MDS) and the method of paired comparisons, and Content Analysis, to the ratings and responses of service research experts. MDS showed that the construct of Customer Contact is multidimensional and complex. An interval scale was developed using the paired comparison methodology, and a measurement model was developed using this contact scale. The central finding was that the degree or level of contact can be measured at the episode level by averaging the normalized values of communication time, the information richness, and the level of intimacy. The uses of the measurement model include refining current research, and reevaluating past research, developing contingency models for service quality and design, and providing practitioners with a richer understanding of customer contact to facilitate service system design.